2021
DOI: 10.1080/08912963.2020.1867982
|View full text |Cite
|
Sign up to set email alerts
|

A comprehensive phylogenetic analysis of coelacanth fishes (Sarcopterygii, Actinistia) with comments on the composition of the Mawsoniidae and Latimeriidae: evaluating old and new methodological challenges and constraints

Abstract: Institutional abbreviations ……………………………………………………………………………………………………………Section 1: Inputs for analyses ………………………………………………………………………………………………………. 1.1. List of characters ……………………………………………………………………………………………………………….. 1.2. Scoring of Mawsonia …………………………………………………………………………………………………………. 1.3. Data matrix and notes ………………………………………………………………………………………………………. 1.4. Stratigraphic occurrences ………………………………………………………………………………………………….. 1.5. R commands for Stratigraphic Tree Analyses …………………………………………………………………….. Section 2: Phylogeneti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
25
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 22 publications
(26 citation statements)
references
References 76 publications
1
25
0
Order By: Relevance
“…Despite their historical notoriety as a species-poor, morphologically conservative lineage, the fossil record of coelacanths has shown that this clade diversified into a wide variety of morphologies in the ancient past [ 17 , 29 , 49 ]. Fossil coelacanths show bursts of species diversity during the Devonian and Triassic [ 83 ] and achieved a high degree of body size variation ranging from diminutive species less than 5 cm long to 6 + m giants representing some of the largest freshwater fishes [ 18 ].…”
Section: Introductionmentioning
confidence: 99%
“…Despite their historical notoriety as a species-poor, morphologically conservative lineage, the fossil record of coelacanths has shown that this clade diversified into a wide variety of morphologies in the ancient past [ 17 , 29 , 49 ]. Fossil coelacanths show bursts of species diversity during the Devonian and Triassic [ 83 ] and achieved a high degree of body size variation ranging from diminutive species less than 5 cm long to 6 + m giants representing some of the largest freshwater fishes [ 18 ].…”
Section: Introductionmentioning
confidence: 99%
“…We can even hypothesize that the Cretaceous distribution of the genera pair is the result of an ancient Pangean distribution and experienced the breakup of the supercontinent. In this case, the closely related Jurassic marine genus Trachymetopon [ 30 , 38 , 108 , 112 , 134 ] should be included in the scenario. But again, a well-supported phylogeny is needed to draw biogeographic models.…”
Section: Discussionmentioning
confidence: 99%
“…The systematics of the Cretaceous mawsoniids is still uncertain, particularly at the specific level, but it is increasingly clear that two sister genera, well supported by all cladistics analyses (e.g. [ 29 , 30 ]), shared their stratigraphic range throughout the Cretaceous: Mawsonia occurred in the Late Jurassic and its range extended until the early Late Cretaceous, while Axelrodichthys is known from the late Early Cretaceous (although the ghost range of its lineage is expected to extend to the Late Jurassic if it is a sister of Mawsonia ) and became extinct in the Late Cretaceous on the basis of our current knowledge [ 28 ].…”
Section: Introductionmentioning
confidence: 99%
“…In other fishes such as sharks, their dorsal fin position is fixed, but the positions of their pectoral fins or body postures are used to express behavioral intentions (Martin, 2007). Interestingly, although their body forms have changed somewhat, the DF of coelacanths has not changed much at all across their 400-millionyear history, while other animal lineages have greatly changed, including diverse fish species radiations and the occurrence of many types of fins in fishes (Casane and Laurenti, 2013;Cavin and Guinot, 2014;Larouche et al, 2017;Toriñoa et al, 2021).…”
Section: Spreading and Folding Of The Coelacanth First Dorsal Finmentioning
confidence: 99%